The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40615-016-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Designing Culturally Relevant Physical Activity Programs for African-American Women: A Framework for Intervention Development

Abstract: Background African American women perform low levels of physical activity and are disproportionally burdened by associated cardiometabolic disease conditions (i.e. 57% are obese, 49% have cardiovascular disease) The marked health disparities among African American women indicate the need for innovative strategies to promote physical activity to help attenuate the chronic disease health disparities in this high-risk population. Culturally tailoring PA programs to address the sociocultural norms, values, beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 119 publications
4
50
0
Order By: Relevance
“…Historically, AA women have been viewed as the primary caretakers of their familial units (ie, family and other kinship-type relationships). 17 This caretaking role is something many AA women take great pride in, and as a result, can limit their available time to engage in PA. 17,24 Previous research indeed shows that some AA women view PA as a self-indulgent or self-serving behavior that takes valuable time away from their family and caretaking responsibilities. 43,44 Together, these phenomena have been termed collectively as an AA woman’s “ethic of care” (referring to the self-sacrificing behaviors of AA women to ensure the needs of their familial and community units are met before their own needs).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, AA women have been viewed as the primary caretakers of their familial units (ie, family and other kinship-type relationships). 17 This caretaking role is something many AA women take great pride in, and as a result, can limit their available time to engage in PA. 17,24 Previous research indeed shows that some AA women view PA as a self-indulgent or self-serving behavior that takes valuable time away from their family and caretaking responsibilities. 43,44 Together, these phenomena have been termed collectively as an AA woman’s “ethic of care” (referring to the self-sacrificing behaviors of AA women to ensure the needs of their familial and community units are met before their own needs).…”
Section: Discussionmentioning
confidence: 99%
“…Potential strategies to leverage these findings in the design of culturally relevant PA program for AA women include incorporating success stories or testimonials from other AA women to instill a sense of self-worth and self-entitlement for PA (ie, aligning with the emotional arousal and verbal persuasion concepts of Self-Efficacy) and emphasizing how PA is relevant to the various caretaking and community roles of AA women (ie, illustrate the importance of PA as a role modeling behavior to others and highlight how being active on a regular basis can result in increased energy that can help women perform their caretaking tasks and their ability to engage with their children,). 17,49 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Faith-based interventions have been successful in reducing weight, improving dietary practices, and increasing physical activity among African American women. 8,9 Previous studies have identified positive linkages between cultural adaptation, spirituality/ religion and social support, and promotion of health-related behaviors among African American women, [10][11][12][13][14][15][16] perhaps through their impact on self-efficacy, selfconfidence, and "normalizing" behaviors through role modeling and accountability partners. Learning and Developing Individual Exercise Skills (L.A.D.I.E.S.)…”
Section: Introductionmentioning
confidence: 99%